Results of the 18-month test with MEA at the post-combustion capture pilot plant at Niederaussem – new impetus to solvent management, emissions and dynamic behaviour. (April 2020) - Moser, Peter; Wiechers, Georg; Schmidt, Sandra; Garcia Moretz-Sohn Monteiro, Juliana; Charalambous, Charithea; Garcia, Susana; Sanchez Fernandez, Eva
Highlights: Continuous long-term testing with 30 wt% MEA over 13, 000 h at a lignite-fired power plant. Low specific MEA consumption of less than 300 g/t CO2 in the linear degradation regime. At the Niederaussem pilot plant thermal degradation is less significant compared to other capture plants. No critical threshold concentration of iron as a possible catalyst for degradation was detected. "Bleed and Feed" as solvent management strategy is not effective, and inferior to ion exchange. Abstract: An almost continuous 13, 000 h long-term testing under real operating conditions was conducted at the post combustion capture pilot plant in the Niederaussem lignite-fired power plant, with a 30 wt% aqueous monoethanolamine (MEA) solvent solution. The capture plant at Niederaussem shows lower solvent consumption and emissions in comparison to other testing facilities, which are also part of the ALIGN-CCUS project (capture plant at Technology Centre Mongstad (NOR), pilot rig at Tiller (NOR), PACT facilities at Sheffield (UK)). One of the key activities of the ALIGN-CCUS project is to investigate how the time-dependent degradation products and trace components that might act as catalysts for degradation develop over long-term operation, as well as which countermeasures against degradation could be applied. Particularly, it was tested if critical threshold values for the iron ion concentration from literature could be confirmed. Therefore, partial solvent inventory replacement by "Bleed and Feed" and solvent reclaiming based on ion exchange were applied. Dedicated test campaigns on the dynamic behaviour of the capture plant were also carried out and MEA emissions under transient conditions were investigated. Important results are: (i) the confirmation of the non-linear degradation behaviour of MEA; (ii) a different degradation behaviour of MEA in comparison to shorter testing campaigns at other pilot plants regarding the main degradation product acetate; (iii) no critical threshold concentration of iron in the solvent was detected; (iv) very low emissions of MEA < 3 mg/m³ and <10 mg/m³ even under transient operating conditions could be reached; and (v) no aerosol formation occurred.